2022
DOI: 10.3389/fnmol.2022.870085
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Alterations and Novel Markers of Neurotoxic Reactive Astrocytes in Human Induced Pluripotent Stem Cell Models

Abstract: Astrocytes respond to injury, infection, and inflammation in the central nervous system by acquiring reactive states in which they may become dysfunctional and contribute to disease pathology. A sub-state of reactive astrocytes induced by proinflammatory factors TNF, IL-1α, and C1q (“TIC”) has been implicated in many neurodegenerative diseases as a source of neurotoxicity. Here, we used an established human induced pluripotent stem cell (hiPSC) model to investigate the surface marker profile and proteome of TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 126 publications
(148 reference statements)
2
13
0
Order By: Relevance
“…1m-n, Extended Data Fig. 2d), corroborating previous reports in the literature demonstrating induction of VCAM1 in astrocytes under pro-inflammatory conditions 33–35 .…”
Section: Resultssupporting
confidence: 90%
“…1m-n, Extended Data Fig. 2d), corroborating previous reports in the literature demonstrating induction of VCAM1 in astrocytes under pro-inflammatory conditions 33–35 .…”
Section: Resultssupporting
confidence: 90%
“…Our transcriptome analysis contained probes for three of these markers (VCAM-1, HLA-E and PDPN) which were all up-regulated by TNFα at 24 h (IFNγ failed to regulate PDPN). The response in our system was characterized by the expression of genes involved in immune effector recruitment and activation, similar to the findings by Labib et al [ 31 ]. The study on TIC-activated ACs identified proteomics-based activation markers.…”
Section: Resultssupporting
confidence: 75%
“…A particular combination of inflammogens, TNFα, IL1α and C1q (termed TIC), has often been used to generate and characterize neurotoxic ACs [ 30 , 66 ]. A recent study on TIC-induced reactive ACs revealed a distinct signature of six cell-surface markers: VCAM-1, BST2, ICOSL, HLA-E, PD-L1 and PDPN after 24 h of stimulation [ 31 ]. Our transcriptome analysis contained probes for three of these markers (VCAM-1, HLA-E and PDPN) which were all up-regulated by TNFα at 24 h (IFNγ failed to regulate PDPN).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations